Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) may reduce the risk of developing cancer-related lymphedema following axillary lymph node dissection (ALND) - Brown, Stav; Tadros, Audree B.; Montagna, Giacomo; Bell, Tajah; Crowley, Fionnuala; Gallagher, Emily J.; Dayan, Joseph H. (Frontiers in Pharmacology, 2024)
Purpose: Patients undergoing axillary lymph node dissection (ALND) for breast cancer face a high risk of lymphedema, further increased by high body mass index (BMI) and insulin resistance. GLP-1 receptor agonists (GLP-1RAs) have the potential to reduce these risk factors, but their role in lymphedema has never been investigated. The purpose of this study was to determine if GLP-RAs can reduce the risk of lymphedema in patients undergoing ALND. Methods: All patients who underwent ALND at a tertiary cancer center between 2010 and 2023 were reviewed. Patients with less than two years of follow-up from the time of ALND were excluded. Race, BMI, radiation, chemotherapy history, pre-existing diagnosis of diabetes, lymphedema development after ALND, and the use of GLP-1RAs were analyzed. Multivariate logistic regression analysis was performed to assess if there was a significant reduction in the risk of developing lymphedema after ALND. A sub-group analysis of non-diabetic patients was also performed. Results: 3830 patients who underwent ALND were included, 76 of which were treated with GLP-1 RAs. The incidence of lymphedema in the GLP-1 RA cohort was 6.6% (5 patients) compared to 28.5% (1071 patients) in the non-GLP-1 RA cohort. On multivariate regression analysis, patients who were treated with GLP-1 RA were 86% less likely to develop lymphedema compared to the non-GLP-1 RA cohort (OR 0.14, 95% CI 0.04-0.32, p<0.0001). A BMI of 25 kg/m 2 or greater was a statistically significant risk factor for developing lymphedema with an odds ratio of 1.34 (95% CI 1.16-1.56, p<0.0001). Diabetes was associated with lymphedema development that closely approached statistical significance (OR 1.32, 95% CI 0.97-1.78, p=0.06). A subgroup analysis solely on non-diabetic patients showed similar results. The odds of developing lymphedema were 84% lower for patients without diabetes treated with GLP1-RAs compared to those who did not receive GLP-1 RAs (OR 0.16, 95% CI 0.05-0.40, p<0.0001). Conclusions: GLP1-RAs appear to significantly reduce the risk of lymphedema in patients undergoing ALND. The mechanism of action may be multifactorial and not limited to weight reduction and insulin resistance. Future prospective analysis is warranted to clarify the role of GLP-1RAs in reducing lymphedema risk.